Electronic structure of tantalum dichalcogenide using Compton scattering technique and density functional theory. (May 2021) - Mali, Deepika; Kumar, Kishor; Jangid, Pawan K.; Arora, Gunjan; Ahuja, B.L.
Abstract: Compton spectroscopy measurements on tantalum dichalcogenide TaS0.5 Se1.5 using a 100 mCi Am-241 γ-ray Compton spectrometer are presented. Experimental Compton profile (CP) is compared with those computed using linear combination of atomic orbitals (LCAO) method within the density functional theory (DFT) and hybrid functionals of Hartree-Fock and DFT. Hybrid functional namely WC1LYP based CP is found in better accordance with the experimental CP. The relative nature of bonding in TaS0.5 Se1.5 and TaSSe is interpreted by scaling the experimental CP on equal-valence-electron-density and Mulliken's population analysis. Origin of metallic behaviour of TaS0.5 Se1.5 is discussed in terms of energy bands and density of states. It is seen that the 5d states of Ta dominate around the Fermi level leading to metallic character of the compound. Fermi surface topology and optical response like dielectric constants, absorption coefficients, etc. of TaS0.5 Se1.5 are also described using modified Becke-Johnson theory of full-potential linearized augmented plane wave approach. Highlights: Measured first-ever Compton profile (CP) of tantalum dichalcogenide TaS0.5 Se1.5 . Compared experimental CPs with those computed using LCAO. Analysed relative nature of bonding of TaS0.5 Se1.5 and TaSSe using EVED profiles and Mulliken's population. Validated use of hybrid WC1LYP exchange-correlation potential to predict electronic response. Discussed Fermi surface topology and optical response of TaS0.5 Se1.5 using FP-LAPW-mBJ approach.